Discovery of an Acyclic Nucleoside Phosphonate that Inhibits Mycobacterium tuberculosis ThyX Based on the Binding Mode of a 5‐Alkynyl Substrate Analogue. Issue 8 (8th July 2013) - Parchina, Anastasia; Froeyen, Matheus; Margamuljana, Lia; Rozenski, Jef; De Jonghe, Steven; Briers, Yves; Lavigne, Rob; Herdewijn, Piet; Lescrinier, Eveline
Abstract The urgent need for new antibiotics poses a challenge to target un(der)exploited vital cellular processes. Thymidylate biosynthesis is one such process due to its crucial role in DNA replication and repair. Thymidylate synthases (TS) catalyze a crucial step in the biosynthesis of thymidine 5‐triphosphate (TTP), an elementary building block required for DNA synthesis and repair. To date, TS inhibitors have only been successfully applied in anticancer therapy due to their lack of specificity for antimicrobial versus human enzymes. However, the discovery of a new family of TS enzymes (ThyX) in a range of pathogenic bacteria that is structurally and biochemically different from the "classic" TS (ThyA) has opened the possibility to develop selective ThyX inhibitors as potent antimicrobial drugs. Here, the interaction of the known inhibitor 5‐(3‐octanamidoprop‐1yn‐1yl)‐2′‐deoxyuridine‐5′‐monophosphate (1) with Mycobacterium tuberculosis ThyX enzyme is explored using molecular modeling starting from published crystal structures, with further confirmation through NMR experiments. While the deoxyuridylate (dUMP) moiety of compound 1 occupies the cavity of the natural substrate in ThyX, the rest of the ligand (the "5‐alkynyl tail") extends to the outside of the enzyme between two of its four subunits. The hydrophobic pocket that accommodates the alkyl part of the tail is formed by displacement of Tyr 44.C, Tyr 108.A and Lys 165.A. Changes to the resonance of the Lys 165 NH3 group upon ligand binding were monitored in a titration experiment by 2D HISQC NMR. Guided by the results of the modeling and NMR studies, and inspired by the success of acyclic antiviral nucleosides, compounds where a 5‐alkynyl uracyl moiety is coupled to an acyclic nucleoside phosphonate (ANP) were synthesized and evaluated. Of the compounds evaluated, sodium (6‐(5‐(3‐octanamidoprop‐1‐yn‐1‐yl)‐2, 4‐dioxo‐3, 4‐dihydropyrimidin‐1(2H)‐yl)hexyl)phosphonate (3 e) exhibited 43 % of inhibitory effect on ThyX at 50 μM. While only modest activity was achieved, this is the first example of an ANP inhibiting ThyX, and these results can be used to further guide structural modifications to this class to develop more potent compounds with potential application as antibacterial agents acting through a novel mechanism of action.